Reading between the lines: exploring the assumptions and implications of parental involvement - Theodorou, Eleni (International Journal about Parents in Education, 2023)
Parental involvement in the Northern American literature has been portrayed as the newly discovered way of improving school effectiveness and academic performance. However the cultural assumptions behind ubiquitous calls for parental involvement have been left largely unexplored. Critics of current notions of “parental involvement” argue that the term itself has been poorly defined in the literature and that it has often been described as an aspired ideal whose demands on the parents and the implications for the nature of home-school relations remain un-scrutinized. This paper seeks to explore existing literature on parental involvement though a cultural lens and draw on theoretical arguments that problematize the assumptions behind the discourse and practice of “parental involvement” or “home-school partnership”. The discussion focuses particularly on the implications that culturally- and class-specific assumptions about parental involvement may have for minority and immigrant families who run the risk of becoming marginalized while being held responsible for getting “involved” (de Carvalho, 2001).